Fish ectoparasite in public aquarium - Radhitia Prasetiawan Nanda; Amalia Kurniasih Ratna; Setiawan Agus; Penataseputro Tanjung (BIO Web of Conferences)
Ectoparasite infestation is a problem related to fish health commonly found in aquaculture activities including ornamental fish that are kept in public aquariums for exhibition. Parasite infestation can trigger various diseases or other health problems. Identification and inventory of ectoparasites become necessary to avoid it. This paper describes the results of ectoparasite inventories in fish that kept in public aquariums facility. An inventory of ectoparasites was carried out through non-lethal sampling using skin scrapping and gill biopsy techniques by wet mount then observed under the microscope. Five groups of parasites (Protozoa, Monogeneans, Digeneas, Copepod, Isopod) infest nine species of fish in the aquarium facilities and dominated by Monogeneans. The highest number of parasite species was detected in seawater quarantine pond. Carassius auratus auratus is a freshwater fish which have the most parasitic infestations. Meanwhile, the seawater fish with the most parasitic infestations was Diodon sp. Parasitic infestation not always shows clinical symptoms. Trachinoctus blochii infested by Cryptocaryon sp. showed skin lesions and became fish have noticeable clinical change. Prevention of the entry of parasites, quarantine processes, and application of systems for breaking the life cycle of parasites important in parasite control in public aquarium.